2008
DOI: 10.1097/gme.0b013e31806bf32c
|View full text |Cite
|
Sign up to set email alerts
|

Associations of blood selenium and serum lipid levels in Japanese premenopausal and postmenopausal women

Abstract: E-Se may be one of the possible associated factors that decrease the levels of TC and LDL-C after menopause. Further studies are needed to clarify the cause-and-effect relationship of nutritional Se status and lipid profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 28 publications
2
22
1
Order By: Relevance
“…They emphasised that serum Se levels could not reflect nutritional Se status in well-nourished humans because serum Se can easily reach a saturated level. In addition, they concluded that serum Se levels could only be useful as a nutritional status indicator in populations where Se intake is insufficient [21]. Because this mechanism may also be valid for Zn and Cu, future studies should evaluate both serum and erythrocyte levels of these trace elements to reveal the relationship of these trace elements to lipids and osteoporosis.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…They emphasised that serum Se levels could not reflect nutritional Se status in well-nourished humans because serum Se can easily reach a saturated level. In addition, they concluded that serum Se levels could only be useful as a nutritional status indicator in populations where Se intake is insufficient [21]. Because this mechanism may also be valid for Zn and Cu, future studies should evaluate both serum and erythrocyte levels of these trace elements to reveal the relationship of these trace elements to lipids and osteoporosis.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, it has been shown that increased Se intake induces increased glutathione peroxidase activity and decreased concentrations of lipid parameters (TC, LDL-C, TG) in animal blood [56,66]. Karita et al [21] in their study reported that lower levels of Se in erythrocytes were associated with higher levels of serum TC and LDL-C and that this relationship was marked only in the postmenopausal group. However, in parallel with our results, they could not find any relation between serum Se level and lipids.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Results from studies predicting heart disease using serum levels of selenium [22][23][24][25] have bee inconsistent. Serum selenium levels of diabetic patients were reported to be increased [30][31][32] decreased [33,34] or unchanged [35] compared to controls. Swapnil Rajpathak et al [20] have found that levels of selenium are lower among diabetic men with or without CVD than among healthy controls, In this study, by contrast between two groups of diabetic patient there is significant decrease in selenium level in group II(diabetic patients with CVD) than in group I(diabetic patients).…”
Section: Resultsmentioning
confidence: 99%
“…Positive relationships between serum selenium and total cholesterol concentrations are discussed in several studies of various serum selenium concentrations [2, 19,32,[36][37][38][39][40][41]43]. However, most participants have been young and middle-aged adults.…”
Section: ----------------------------------------mentioning
confidence: 99%